Social support score in patients with malignant diseases—with sociodemographic and medical characteristics - Corovic, Snezana; Vucic, Veroljub; Mihaljevic, Olgica; Djordjevic, Jelena; Colovic, Sofija; Radovanovic, Snezana; Radevic, Svetlana; Vukomanovic, Ivana Simic; Janicijevic, Katarina; Sekulic, Marija; Djukic, Svetlana; Vukomanovic, Vladimir; et al. (Frontiers in Psychology, 2023)
Social support is considered a complex construct that has positive effects on patient well-being and emotional adjustment to cancer. The aim of this study is to examine the level of social support in oncology patients and its correlation with sociodemographic and medical variables. Method: The research was conducted in the form of a prospective observational study in 2020, which included patients aged 19 and older with a diagnosis of oncological disease. The research was conducted in the General Medicine Service at the Trstenik Health Center, Central Serbia, after approval by the Ethics Committee of the Health Center Trstenik, Central Serbia. A questionnaire for assessing social support (Oslo-3 Social Support Scale) was used as a research instrument. Results: The obtained values at the level of the entire study population point to poor social support in nearly 90% of cases. Regression analysis showed that gender, education, self-assessment of health, impact of pain on performing activities, unfulfilled needs for health care, means of information, anxiety score and depression score have a statistically significant influence on the social support score. Conclusion: Interventions to improve social support may be helpful in improving mental health and quality of life in cancer patients.